2011
DOI: 10.1111/j.1439-0310.2011.01960.x
|View full text |Cite
|
Sign up to set email alerts
|

Spider Males Adjust Mate Choice but Not Sperm Allocation to Cues of a Rival

Abstract: Spatial and temporal variation in ecological parameters selects for plastic responses to prevailing conditions. Males of web spiders have been shown to adjust developmental decisions to cues that relate to the degree of competition from other males. Here, we explore experimentally whether males of the spider Nephila senegalensis base behavioural decisions in the context of mate choice and sperm allocation to the presence of cues of a rival and to their own competitive dominance. Large and small males were offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 56 publications
(96 reference statements)
0
23
0
Order By: Relevance
“…This is unlike in Nephila senegalensis , another spider with a similar mating system, in which males have been found to avoid competition (Schneider et al. ) in a similar laboratory setting. Likewise, a study using the Australian N. plumipes found that males tend to avoid competitive situations when the context changes (Jordan et al.…”
Section: Discussionmentioning
confidence: 93%
“…This is unlike in Nephila senegalensis , another spider with a similar mating system, in which males have been found to avoid competition (Schneider et al. ) in a similar laboratory setting. Likewise, a study using the Australian N. plumipes found that males tend to avoid competitive situations when the context changes (Jordan et al.…”
Section: Discussionmentioning
confidence: 93%
“…In a mate-choice context, there is some evidence that individuals are able to assess competition for potential mates: when given a choice between females that are associated with other males and hence the subject of higher perceived sperm competition, males of some species prefer females subject to lower competition, for example, Poecilia reticulata (Dosen and Montgomerie 2004) and Gambusia holbrooki (Wong and McCarthy 2009). Further, previous studies of a closely related species to that used in this study, Nephila senegalensis, show that males avoid webs of females that have been previously visited by other males (Schneider et al 2011). However, in our experiments, males on average moved to places with more competitors than would be encountered under random movement.…”
Section: Discussionmentioning
confidence: 96%
“…Males cease web building after reaching maturity and occasionally feed on prey caught by the female. Females are always receptive and accept several males for mating (Schneider, Lucass, Brandler, & Fromhage, 2011;Schneider & Michalik, 2011). Males transfer sperm to the females' paired sperm stores (spermathecae) and eggs are not fertilized until they are laid.…”
Section: Study Species Origin and Rearing Of Study Animalsmentioning
confidence: 99%